The pulmonary-proteoliposome as a new therapeutic approach for Coronaviruses - Feliciello, Isidoro (Hum Vaccin Immunother, 2020)
We are proposingÂ the use of pulmonary-proteoliposome as a new therapeutic approach for Coronaviruses. The designed strategy represents a potential treatment to reduce the overall viral load in the lungs and to help the immune system to successfully stave off the infection.